A Tale of Two Riots The synkrisis of the Temples of Ephesus and Jerusalem in Acts 19–23 - Tripp, Jeffrey M. 1978- (2014)
Towards the end of Paul’s career, Acts narrates two riot scenes tied to the temples in Ephesus and Jerusalem, forming a synkrisis between the two cities and their temples. The similarities between the two scenes argue for temples as places of danger for Christians while protecting the Christian community from perceptions of anti-cultic teaching. The endings, however, are very different. In the ﬁrst case, the correct response to the church is presented in Ephesus where the riot ends in a quick and orderly manner. In the second case, the incorrect response is presented in Jerusalem where the disorder spreads to the local government, forcing the Roman military to intervene.
Keywords: Temple of Artemis; synkrisis; Paul; Jerusalem Temple; Ephesus; Acts